Enhancing nutrition: a review of provitamin A carotenoid cassava breeding initiatives in East Africa - Abincha, W.; Dzidzienyo, D.K.; Wesonga, L.N.; Mwimali, M.; Ozimati, A.; Kayondo, S.I.; Ofori, K.; Tongoona, P.; Kivuva, B.M. (2024)
Biofortification of staple food stands as one of the most reliable methods of alleviating vitamin A deficiency (VAD). Evidence suggests that introducing provitamin A carotenoid (pVAC) cassava into the diets of preschool and primary school children in East Africa has led to improvements in their retinol levels. Notably, Kenya and Uganda have initiated cassava biofortification programs in the region. These efforts involve the assembly and characterization of pVAC cassava germplasm, alongside the development of essential tools such as genomic prediction (GP) models and molecular markers for accelerating genetic gains in the biofortification programs. However, several challenges have emerged, including a negative correlation between carotenoid content and dry matter content in cassava roots, diseases, the absence of affordable high-throughput phenotyping methods, poor cassava flowering, poor pollen viability, low capacity in bioinformatics analyses, degradation of carotenoids during processing, and inadequate germplasm conservation facilities. To address these hurdles, cassava breeding programs in the region require enhanced infrastructure and human capacity to optimize efficiency in cassava biofortification with pVACs.